Pemanfaatan Sampah Plastik dengan Metode Ecobrick Sebagai Upaya Mengurangi Limbah Plastik di Kelurahan Lubang Panjang, Kecamatan Barangin Kota Sawahlunto - welis, wilda; Abel Delingga; Adyka Agung P; Bunga Nur M; Hesti Lisnawati S; Haniffahturrahma (Jurnal IKEOR, 2025)
The problem of plastic waste has become a pressing global issue, requiring concrete solutions from all levels of society. Kajen Village, located in Talang District, Tegal Regency, is also facing this challenge. This paper aims to explore the potential of utilizing p lastic waste through the Ecobrick method as an alternative measure to reduce the impact of plastic waste in the region. The Ecobrick method itself involves compacting plastic waste into used bottles, forming environmentally friendly "bricks" that can be used as building materials. This activity was carried out through a community service approach, involving the active participation of Kajen Village residents. The initial step was a preliminary study to determine the type and volume of plastic waste produced, as well as the level of public awareness of the dangers of plastic waste to the environment. Next, education and outreach were conducted to the community regarding the importance of plastic waste management and the benefits of Ecobricks, which they can implement independently. The community service program also included training and technical assistance so that residents could make Ecobricks correctly and safely. Collaboration with the village government and environmental organizations contributed to the success and broader understanding of the urgency of plastic waste reduction. Regular monitoring and evaluation processes are conducted to assess the program's impact and improve its effectiveness. Results from these activities demonstrate increased community understanding of the plastic waste problem and high enthusiasm for producing and utilizing Ecobricks for local development. The active involvement of the village government and collaboration with relevant agencies opens up opportunities for program development toward more sustainable solutions.